Proceedings of the 3rd Annual International Conference on Public and Business Administration (AICoBPA 2020) 2021
DOI: 10.2991/aebmr.k.210928.020
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Perceived Organizational Support and Proactive Personality on Organizational Commitment and Organizational Citizenship Behavior Among Banking Employees in Malang

Abstract: In current banking industry competition, not only support from the organization are needed by employees to increase commitment and organizational citizenship behaviour (OCB), but also the employees' personality itself are important. Using social exchange theory, this research aims to determine the effect of organizational support (POS) and proactive personality on commitment and OCB. Quantitative explanatory approach and Partial Least Square Structural Equation Modelling (PLS-SEM) are used in this research. Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…The effect of Organizational Support on Organizational Commitment Organizational support plays a crucial role in increasing commitment in the organization. Idzna et al (2020) stated that in banking industry competition, not only support from the organization is needed by employees to increase commitment and organizational citizenship behavior (OCB), but also the employees' personality itself are important. This study found that support within the organization will significantly increase organizational commitment.…”
Section: H2: Service Orientation Has a Positive And Significant Effec...mentioning
confidence: 99%
“…The effect of Organizational Support on Organizational Commitment Organizational support plays a crucial role in increasing commitment in the organization. Idzna et al (2020) stated that in banking industry competition, not only support from the organization is needed by employees to increase commitment and organizational citizenship behavior (OCB), but also the employees' personality itself are important. This study found that support within the organization will significantly increase organizational commitment.…”
Section: H2: Service Orientation Has a Positive And Significant Effec...mentioning
confidence: 99%